The utilisation of online alternative media towards participatory democracy: a Malaysian case / Azlina Kamaruddin, Rahmat Ghazali and Mariah Muda - Kamaruddin, Azlina; Ghazali, Rahmat; Muda, Mariah (2016)
This study examines the utilisation of online alternative media towards participatory democracy. Since the enactment of the Communication and Multimedia Act 1999, online alternative media such as Malaysiakini, Malaysia Today, and the Malaysian Insider have played a pivotal role in many political events including the post-Mahathir-Anwar political crisis, the 2008 financial crisis, election campaign, Anwar’s sodomy case, and Dr. Hasan Ali’s disclosure of PAS weaknesses. This study has explored the role of online alternative media and answered the enquiry of how Malaysians have utilised it for participatory democracy. The specific objective of this study to comprehend how public corresponds to online alternative media towards participatory democracy. This study employed qualitative content analysis as data analysis technique. The findings imply that participatory democratic stance via the alternative media is less significant.